Batik Kendil Emas sebagai Warisan Budaya Kabupaten Kendal - Suparti; Parti, Suparti (Fakultas Komputer Dan Desain, 2025)
This study examines Batik Kendil Emas as an Indonesian cultural heritage recognized by UNESCO. This batik was launched by Kendal Regency on November 20, 2024, and is inspired by the folktale